ANALISIS HUBUNGAN HASIL BELAJAR DENGAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI HIDROLISIS GARAM. - neti afrianis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Critical thinking skills is a very important aspect that students must have in learning chemistry, especially in solving problems that require deeper alternative solutions. This research aims to analyze the relationship of critical thinking on student learning outcomes on salt hydrolysis material. In this research, there were 48 students sampled, the technique used for sampling was purposive sampling. For data analysis in this research using correlation and regression tests with a probability value of 0.05. From the results of the linearity and correlation tests found that students 'critical thinking skills have a relationship with student learning outcomes on salt hydrolysis material by 0.599 and the regression results also show the same thing that there is a significant relationship between students' critical thinking skills with learning outcomes on salt hydrolysis material that is seen from the comparison of the significance value (0,000) with a probability value (0.05), (0,000 <0.05) means that there is a positive relationship between critical thinking skills with student learning outcomes on salt hydrolysis material in SMAN 1 Kampar. The contribution or contribution of students' critical thinking skills to learning outcomes in the hydrolysis material is 35.9% while the remaining 64.1% is influenced by other factors. The higher the level of critical thinking skills of students, the greater the significant functional relationship to learning outcomes, and also the greater contribution / contribution of critical thinking skills to student learning outcomes.Keywords : Critical thinking skills, learning outcomes, correlation and regression analysis, salt hydrolysis